Differential Expression of Two Novel Members of the Tomato Ethylene-Receptor Family - Tieman, Denise M. (American Society of Plant Physiologists, 1999)
The phytohormone ethylene regulates many aspects of plant growth, development, and environmental responses. Much of the developmental regulation of ethylene responses in tomato (Lycopersicon esculentum) occurs at the level of hormone sensitivity. In an effort to understand the regulation of ethylene responses, we isolated and characterized tomato genes with sequence similarity to the Arabidopsis ETR1 (ethylene response 1) ethylene receptor. Previously, we isolated three genes that exhibit high similarity to ETR1 and to each other. Here we report the isolation of two additional genes, LeETR4 and LeETR5, that are only 42% and 40% identical to ETR1, respectively. Although the amino acids known to be involved in ethylene binding are conserved, LeETR5 lacks the histidine within the kinase domain that is predicted to be phosphorylated. This suggests that histidine kinase activity is not necessary for an ethylene response, because mutated forms of both LeETR4 and LeETR5 confer dominant ethylene insensitivity in transgenic Arabidopsis plants. Expression analysis indicates that LeETR4 accounts for most of the putative ethylene-receptor mRNA present in reproductive tissues, but, like LeETR5, it is less abundant in vegetative tissues. Taken together, ethylene perception in tomato is potentially quite complex, with at least five structurally divergent, putative receptor family members exhibiting significant variation in expression levels throughout development.